2013
DOI: 10.1007/s10433-013-0265-9
|View full text |Cite
|
Sign up to set email alerts
|

Prospective memory tasks related to goals and concerns are rated as more important by both young and older adults

Abstract: There has been little research on variables that affect importance ratings for real prospective memory tasks (e.g., remembering to take medications). Our primary purpose was to test a claim in the motivational-cognitive model of prospective memory, namely that prospective memory tasks highly related to a person's goals and concerns will be rated as more important. We also tested whether this relationship held in both young and older adults. A secondary purpose was to investigate age-related differences in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Finally, although we are unaware of any findings showing gender differences in importance effects in PM (i.e., gender by importance interactions), we did test for gender effects. Past findings on other aspects of PM have shown a fairly consistent pattern, with females outscoring males on perceived task importance (Penningroth & Scott, 2013), strategy use (Soler & Ruiz, 1996;Uttl & Kibreab, 2011;Yoder & Herrmann, 2003), and actual performance (e.g., Huppert, Johnson, & Nickson, 2000;Maylor & Logie, 2010). However, because there is still little research on gender differences in PM generally and none on the questions we posed, these analyses were exploratory.…”
mentioning
confidence: 79%
See 3 more Smart Citations
“…Finally, although we are unaware of any findings showing gender differences in importance effects in PM (i.e., gender by importance interactions), we did test for gender effects. Past findings on other aspects of PM have shown a fairly consistent pattern, with females outscoring males on perceived task importance (Penningroth & Scott, 2013), strategy use (Soler & Ruiz, 1996;Uttl & Kibreab, 2011;Yoder & Herrmann, 2003), and actual performance (e.g., Huppert, Johnson, & Nickson, 2000;Maylor & Logie, 2010). However, because there is still little research on gender differences in PM generally and none on the questions we posed, these analyses were exploratory.…”
mentioning
confidence: 79%
“…Past findings on other aspects of PM have shown a fairly consistent pattern, with females outscoring males on perceived task importance (Penningroth & Scott, 2013), strategy use (Soler & Ruiz, 1996;Uttl & Kibreab, 2011;Yoder & Herrmann, 2003), and actual performance (e.g., Huppert, Johnson, & Nickson, 2000;Maylor & Logie, 2010). Past findings on other aspects of PM have shown a fairly consistent pattern, with females outscoring males on perceived task importance (Penningroth & Scott, 2013), strategy use (Soler & Ruiz, 1996;Uttl & Kibreab, 2011;Yoder & Herrmann, 2003), and actual performance (e.g., Huppert, Johnson, & Nickson, 2000;Maylor & Logie, 2010).…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…The Virtual Week training program was similar to the original, computerized version of the game (Rendell et al, 2007;Rose et al, 2010) except that the time-based tasks in this study required monitoring a clock that indicated the virtual time of day rather than having the times marked on squares of the board (similar to recent Virtual Week studies, e.g., Leitz et al, 2009;Rendell et al, 2011), and the task content varied over the 24 virtual days. Many of the PM tasks simulated actual PM tasks that a sample of older adults (mean age = 75.4 years) reported in a survey study (Penningroth and Scott, 2013). Importantly, task difficulty increased over the 24 virtual days.…”
Section: Virtual Week Training Programmentioning
confidence: 92%